How does the global plastic waste trade contribute to environmental benefits: Implication for reductions of greenhouse gas emissions?. (1st June 2021) - Liu, Zhe; Liu, Weili; Walker, Tony R.; Adams, Michelle; Zhao, Jingjing
Abstract: Plastic waste pollution has been identified as a serious global issue, posing environmental risks in terms of massive waste generation, ocean pollution, and increases in greenhouse gas (GHG) emissions. Despite documented environmental impacts, it remains debatable whether the global plastic waste trade (GPWT) for reutilization and recycling, as part of the global circular economy (CE), has historically contributed to environmental benefits. To investigate if historical GPWT has contributed to environmental benefits in terms of reductions of GHG emissions, this study analyzed GPWT between China and trading countries through their trajectories, characteristics and driving forces of reductions of GHG emissions between 1992 and 2017. Results indicated an increasing trend of reductions of GHG emissions in GPWT between China and trading countries over 25 years. A net reduction of 8.27 million metric tons carbon dioxide equivalent (CO2 e) was observed in 2012, nearly 84 times levels observed in 1992. Policy implications after China's recent ban of imports of GPWT in December 2017 and recent changes of GPWT to other Asian countries are discussed. Dramatic changes in sustainable approaches to GPWT for reutilization and recycling are required. Graphical abstract: Image 1 Highlights: Plastic waste generation and its connection with circular economy are introduced. Results indicated that the GPWT for reutilization reduced GHG emissions. A highest net reduction of 8.27 million MT CO2 e was observed in 2012. Policy implications for global plastic waste trade for reutilization are proposed.